Surface integrity characterization of ground hardened H13 hot die steel using different lubrication environments - Awale A.; Srivastava A.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
Surface integrity has a significant effect on the service life of manufactured component as poor surface integrity may cause failure of produced component during its service life. Grinding is the last processing operation during manufacturing cycle of components, which decides the surface integrity of manufactured component. Surface quality of a component depends on the lubricating and cooling effect of cutting fluids during grinding. Thus, the present research work focused on an experimental study the effect of different lubrication modes like dry, flood, minimum quantity lubrication (MQL) on the surface properties of ground hardened H13 hot die steel. Surface integrity was evaluated in terms of surface roughness and microhardness of ground surface, ground surface topography, and microchip morphology. Whereas, grinding performance was evaluated in terms of grinding force. The surface topography and elemental composition of ground surface along with microchip were observed using scanning electron microscope (SEM), atomic force microscope (AFM), and energy dispersive x-ray spectroscopy (EDX). Experimental results indicated that MQL with castor oil (CO) provided lowest surface roughness and grinding forces among all lubrication conditions, which were R a: 0.245 μm, R z: 1.846 μm, F t: 30.65 N, and F n: 42.35 N, respectively. According to AFM analysis, poor surface quality (deep grooves and furrows) was observed under dry grinding due to micro-fractured abrasive grains and hard microchip rubbed over the ground surface. Continuous and smooth (no wear track) microchip was observed with MQL-CO lubrication. Further, EDX analysis indicated that microchips obtained upon MQL-CO lubrication were having very less carbon peaks without any surface oxidation. Higher microhardness was observed with MQL-DIW cooling due to suddenly quenching effect over the nascent ground surface. © 2018 IOP Publishing Ltd.